2021
DOI: 10.3390/ijerph18052457
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Forest Activities in a University Campus Forest on Student’s Psychological Effects

Abstract: This study aimed to examine the psychological effects of forest activities in a campus forest. A pre-test and post-test control group design was employed to evaluate the psychological effect of forest activities in a campus forest. A total of 38 participants participated in this study (19 in the forest activities group; 19 in the control group). The Profile of Mood State (POMS) questionnaire, the Concise Measure of Subjective Well-Being (COMOSWB), and the modified form of the Stress Response Inventory (SRI-MF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 104 publications
(93 reference statements)
1
46
0
Order By: Relevance
“…Moreover, subjects reported a reduction in stress after connecting to nature. This is consistent with the results obtained by previous research, according to which forest activities can improve mental health [40], reduce depression [41], and promote learning motivation and learning engagement [47,48]. These findings imply that regular exposure to nature for four weeks can improve an individual's mental wellbeing and learning attitude.…”
Section: Cumulative Frequency Doses Of Natural Benefits In Different ...supporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, subjects reported a reduction in stress after connecting to nature. This is consistent with the results obtained by previous research, according to which forest activities can improve mental health [40], reduce depression [41], and promote learning motivation and learning engagement [47,48]. These findings imply that regular exposure to nature for four weeks can improve an individual's mental wellbeing and learning attitude.…”
Section: Cumulative Frequency Doses Of Natural Benefits In Different ...supporting
confidence: 92%
“…Engaging in walking in the forest [40,41] or viewing the forest landscape [42] can induce a positive mood, reduce depression, and improve physiological responses, such as lower blood pressure and heart rate, higher parasympathetic nervous activity, and lower sympathetic nervous activity. For instance, Kim et al [41] examined the impact of forest activities on college students' psychological responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study performed in South Korea, 38 university students with a mean age of around 22 years, with 24 males and 14 females, were assigned in equal numbers to a forest therapy group or a control group [ 76 ]. The experimental group performed eight, one-hour-long sessions once a week according to a structured program but without active guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Forest activities have a positive effect on the psychological aspect of college students [ 49 ], as shown in studies in which intervention through forests plays a beneficial mediating role in mental health such as stress and anxiety [ 50 , 51 ]. In addition, a study showed increases in physiological well-being when walking after appreciating bamboo forest paths for 15 min [ 52 ], and a study showed that forest rest environments using virtual reality have a physiological positive effect on the human body [ 53 ].…”
Section: Discussionmentioning
confidence: 99%